2012
DOI: 10.1111/j.1751-7176.2011.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Efficacy and Safety of Triple‐Combination Therapy With Olmesartan Medoxomil and Amlodipine Besylate and Hydrochlorothiazide for Hypertension

Abstract: Most patients with hypertension require combination therapy in order to achieve blood pressure (BP) goals. This 40-week open-label extension of the 12-week double-blind Triple Therapy With Olmesartan Medoxomil, Amlodipine, and Hydrochlorothiazide in Hypertensive Patients Study (TRINITY) evaluated the efficacy and safety of triplecombination treatments with olmesartan medoxomil, amlodipine besylate, and hydrochlorothiazide (OM ⁄ AML ⁄ HCTZ) in 2112 participants with moderate to severe hypertension. Following 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
(102 reference statements)
2
17
0
Order By: Relevance
“…Adverse effects reported in our study were mild and well tolerated and no discontinuation was needed. Several previous studies also showed well tolerability of triple drug combination 13,20 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Adverse effects reported in our study were mild and well tolerated and no discontinuation was needed. Several previous studies also showed well tolerability of triple drug combination 13,20 .…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, adding thiazide-like diuretics [such as Chlortalidone (12.5-25.0 mg once daily) or Indapamide (1.5 mg modified-release or 2.5 mg once daily)] is suitable as a third-line agent introduced at Step 314. In a study Kereiakes et al 20 Adding another class of medication would be an alternative strategy, although the guidelines do not indicate clearly the third choice for uncontrolled hypertension. In these patients, -blockers seem to be more effective than increasing the dose of either ACE inhibitors or CCB 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In an open-label extension of the randomized trial with olmesartan, amlodipine, and hydrochlorothiazide, all study participants were switched to the triple-drug combination at the conclusion of their 12-week double-blind treatment period and were followed for an additional 40 weeks. 60 No new safety concerns were identified, and 55% and 64% of study participants achieved their BP goal within 2 weeks of starting and by the end of the open-label period/early termination, respectively. Mean BP reduction at the end of the open-label period/ early termination was comparable with that seen in study participants receiving triple-drug therapy during the double-blind treatment period, demonstrating the safety, antihypertensive efficacy, and durability of this triple-drug combination.…”
Section: Cv-relatedmentioning
confidence: 96%
“…Mean BP reduction at the end of the open-label period/ early termination was comparable with that seen in study participants receiving triple-drug therapy during the double-blind treatment period, demonstrating the safety, antihypertensive efficacy, and durability of this triple-drug combination. 60 In the open-label study evaluating aliskiren, amlodipine, and hydrochlorothiazide, this triple-combination therapy was shown to be well tolerated and efficacious as a treatment for up to 54 weeks in patients with hypertension. 61 As a result of these evaluations, the U.S. Food and Drug Administration has approved all 3 of these triple-drug combinations for the management of hypertension as single-pill fixed-dose formulations in patients not controlled on dual therapy.…”
Section: Cv-relatedmentioning
confidence: 99%
“…In this case, the most commonly used drugs are ARBs and ACE inhibitors, Ca 2+ channel blockers (CCB) and diuretics [130] . Long-term treatment triple therapy with olmesartan medoxomil (ARB), amlodipine besylate (CCB) and hydrochlorothiazide (diuretic) in 2112 hypertensive patients with moderate to severe hypertension resulted in 44.5%-79.8% of participants having a decreased the mean blood pressure from 168.6/100.7 mm Hg to 125.0-136.8/77.8-82.5 mmHg, reaching the blood pressure goal [133] . The same triple therapy also proved to be efficient in hypertensive Hispanic/Latin patients [134] .…”
Section: New Targets For Hypertension Treatmentmentioning
confidence: 99%